EFEKTIFITAS PENERAPAN TILANG ELEKTRONIK TERHADAP PELANGGARAN LALU LINTAS DI WILAYAH HUKUM POLDA METRO JAYA - Erik Suriadi; Kristiawanto; Santrawan T. Paparang (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
The use of motorized vehicles in everyday life can have a negative impact, namely congestion and traffic accidents resulting from traffic violations so that it requires law enforcement efforts which are currently using electronic ticketing, but it can become aproblem if the motorized vehicle involved in traffic violations has change ownership or be driven by someone else. This research is anempirical juridical study using a case approach. Data collection techniques through field research. The results showed that the effectiveness of the application of electronic ticketing against traffic violations in the jurisdiction of Polda Metro Jaya has notbeen maximal in overcoming traffic violations because the ETLE camera can only detect certain types of violations. Factors thataffect the effectiveness of the application of Electronic Tickets are legal substance factors that have not been regulated in the Chief of Police Regulation, law enforcement factors, facilities or facilities factors, community legal culture factors, and natural or environmental factors.